2016
DOI: 10.1089/ars.2015.6459
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-1 Attenuates Ventricular and Mitochondrial Postischemic Dysfunction in the Stunned Myocardium of Transgenic Mice

Abstract: These results strongly suggest that Trx1 ameliorates the myocardial effects of I/R by improving the free radical-mediated damage in cardiac and mitochondrial function, opening the possibility of new therapeutic strategies in coronary artery disease. Antioxid. Redox Signal. 25, 78-88.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…High levels of ROS resulted in loss of Trx-1, which was demonstrated by Perez et al, 120 min after reperfusion. Loss of Trx-1 then leads to an ''over''-adaptive response, which explains the opposite finding of an increase of Trx-1 24 h after the reperfusion phase (80). Analyzing Trx-1 levels in cardiac tissue biopsies collected from cardiopulmonary bypass surgeries revealed an increase of Trx-1 in patients who were preconditioned by four cycles of 5 min upper arm ischemia followed by a 5 min reperfusion phase (113).…”
Section: Role Of Trx-1 In I/r In the Heartmentioning
confidence: 99%
“…High levels of ROS resulted in loss of Trx-1, which was demonstrated by Perez et al, 120 min after reperfusion. Loss of Trx-1 then leads to an ''over''-adaptive response, which explains the opposite finding of an increase of Trx-1 24 h after the reperfusion phase (80). Analyzing Trx-1 levels in cardiac tissue biopsies collected from cardiopulmonary bypass surgeries revealed an increase of Trx-1 in patients who were preconditioned by four cycles of 5 min upper arm ischemia followed by a 5 min reperfusion phase (113).…”
Section: Role Of Trx-1 In I/r In the Heartmentioning
confidence: 99%
“…The understanding of post-ischemic events remains critical for the development of novel therapeutic approaches in ischemia-reperfusion pathologies. Although redox proteins in IR have been intensely studied, most of the research has focused on the primarily affected organ as the main injured tissue (Shau et al 2000;Matsushima et al 2006;Godoy et al 2011b;Romero et al 2015;Perez et al 2016). Remote organ responses of redox regulatory proteins after IR, on the other side, represent an unexplored but yet exciting area of research that may broaden our understanding of redox regulation in the multi-systemic conditions encountered in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased apoptosis levels were observed for PRDX6 in vitro in SCOV-3 cell lines treated with cisplatin [ 169 ], for PRDX5 in human tendon fibroblasts treated with H 2 O 2 [ 161 ], and in HT29 cells treated with shikonin [ 166 ], for TRX1 in WEHI7.2 lymphoma cells treated with H 2 O 2 [ 220 ], in in vivo studies on transgenic mice that were treated with methamphetamine [ 214 ], and for SRXN1 in retinal ganglion cells (RGC) of mice treated with high glucose concentrations [ 229 ]. Among the positive effects of overexpression, for PRDX5 , researchers have shown decreased DNA damage in hamster cell cultures CHO-K1 exposed to H 2 O 2 and tert-butylhydroperoxide (tBHP) [ 162 ] as well as for TRX1 in the mitochondria of transgenic mice Trx1-Tg in vivo in sepsis-induced myocardial dysfunction and sham surgery [ 216 , 217 ]. Increased expression of TRX1 in mice in vivo [ 217 ] and ex vivo [ 218 ] decreased the negative consequences of ischemia for the cardiovascular system.…”
Section: Effects Of Antioxidant Defense Gene Overexpression On Stress...mentioning
confidence: 99%
“…Among the positive effects of overexpression, for PRDX5 , researchers have shown decreased DNA damage in hamster cell cultures CHO-K1 exposed to H 2 O 2 and tert-butylhydroperoxide (tBHP) [ 162 ] as well as for TRX1 in the mitochondria of transgenic mice Trx1-Tg in vivo in sepsis-induced myocardial dysfunction and sham surgery [ 216 , 217 ]. Increased expression of TRX1 in mice in vivo [ 217 ] and ex vivo [ 218 ] decreased the negative consequences of ischemia for the cardiovascular system. Using oxygen–glucose deprivation/reoxygenation in in vitro experiments showed that the ability of PON2 to enhance glucose transport and to suppress oxidative stress and apoptosis is potentially a good set of properties to prevent cerebral ischemia-reperfusion injury [ 143 ].…”
Section: Effects Of Antioxidant Defense Gene Overexpression On Stress...mentioning
confidence: 99%
See 1 more Smart Citation